PENERAPAN TEKNIK DEFORMASI BENDA GEOMETRI PADA LAMPU DINDING - Fatmasari, Christine; Juliyanto, Bagus; Ubaidillah, Firdaus (Majalah Ilmiah Matematika dan Statistika, 2021)
In general, the wall lamp has a function as lighting. Wall lamps consist of lamp shades, connectors and stands. This study aims to obtain calculation methods for designing more varied lamp shades, connectors and stands. This research method is divided into several stages. First, build some basic objects as components of wall lamps from cone deformation, ten-prism prisms, tubes and beams with Bezier curve. Second, it arranges several basic objects of wall lamp components on the modeling axis. Third, arrange a program. The results of this study obtained calculation methods for designing various forms of constituent components of wall lamps from conical base objects, triangular prisms, tubes and beams. Furthermore, assembling the components of wall light on modeling axis.